2012
DOI: 10.1242/dev.078501
|View full text |Cite
|
Sign up to set email alerts
|

Onecut transcription factors act upstream of Isl1 to regulate spinal motoneuron diversification

Abstract: SUMMARYDuring development, spinal motoneurons (MNs) diversify into a variety of subtypes that are specifically dedicated to the motor control of particular sets of skeletal muscles or visceral organs. MN diversification depends on the coordinated action of several transcriptional regulators including the LIM-HD factor Isl1, which is crucial for MN survival and fate determination. However, how these regulators cooperate to establish each MN subtype remains poorly understood. Here, using phenotypic analyses of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 55 publications
9
86
0
Order By: Relevance
“…2 A and B). In support of these findings, a recent study demonstrated that Onecut factors directly regulate Isl-1 expression and maintain Isl-1 production during motor neuron diversification (9). These results suggest that the neurogenic-togliogenic transition in NSPCs, and at least a part of neuron-subtype specification, are independently regulated downstream of Coup-tfs.…”
Section: Mir-17mentioning
confidence: 60%
“…2 A and B). In support of these findings, a recent study demonstrated that Onecut factors directly regulate Isl-1 expression and maintain Isl-1 production during motor neuron diversification (9). These results suggest that the neurogenic-togliogenic transition in NSPCs, and at least a part of neuron-subtype specification, are independently regulated downstream of Coup-tfs.…”
Section: Mir-17mentioning
confidence: 60%
“…This conclusion is further supported by the overlap of genes affected in the retinas of single-knockouts, and by the fact that although a larger number of genes demonstrated significant changes of expression in DKO retinas, most of these genes also showed the same direction of changes in the single-knockout retinas. The severity of retinal phenotypes in the three different mutants correlated well with the levels of expression of the two factors (15) also function redundantly in the developing motor neurons in the spinal cord (12). It is likely that the two factors regulate downstream genes in a similar fashion in other developing tissues.…”
Section: Discussionmentioning
confidence: 84%
“…The members of the "onecut" family of transcription factors play diverse developmental roles (8)(9)(10)(11)(12). In the mouse, three onecut factors, Onecut1 (Oc1), Onecut2 (Oc2), and Onecut3 (Oc3), with essentially identical DNA-binding domains exist (13).…”
mentioning
confidence: 99%
“…By electroporation it is possible to induce the expression of specific genes on dissociated primary cell cultures (in vitro) (Zeitelhofer et al, 2007), organotypic cultures (ex vivo) (Pakan and McDermott, 2014) or in living organisms (in utero or in ovo, when treating mammalian embryos in the uterus or animals developing in egg, respectively) (Bony et al, 2013;Odani et al, 2008). Previous studies have explored the role of many proteins involved in MNs fundamental cellular process, such as axon pathfinding (Winning and Krull, 2011), differentiation (Roy et al, 2012), and survival (Choi et al, 2006(Choi et al, ,2013 employing IOE to overexpress the probe genes.…”
Section: Introductionmentioning
confidence: 99%